2019
DOI: 10.1021/acs.jcim.9b01025
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Binding Mechanism of GABAB Receptor Agonists and Antagonists through in Silico Simulations

Abstract: GABA B is a G protein-coupled receptor that functions as a constitutive heterodimer composed of the GABA B1a/b and GABA B2 subunits. It mediates slow and prolonged inhibitory neurotransmission in the nervous system, representing an attractive target for the treatment of various disorders. However, the molecular mechanism of the GABA B receptor is not thoroughly understood. Therefore, a better description of the binding of existing agonists and antagonists to this receptor is crucial to improve our knowledge ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…Additional mutational studies followed by radioligand binding assays showed that mutating Ser130 to Ala abolished binding of the antagonist CGP54626, while mutation of Ser153 were found to affect the affinity of various ligands differently and are thereby suggested to play a role in selectivity of GABA B ligand recognition [51]. For more details about ligand interactions in the orthosteric binding site, please see [36,[51][52][53]. Ligand interactions with residues located in LB2 seem to be restricted to agonists and high-affinity antagonists [36,52,53].…”
Section: Orthosteric Binding Sitementioning
confidence: 99%
See 3 more Smart Citations
“…Additional mutational studies followed by radioligand binding assays showed that mutating Ser130 to Ala abolished binding of the antagonist CGP54626, while mutation of Ser153 were found to affect the affinity of various ligands differently and are thereby suggested to play a role in selectivity of GABA B ligand recognition [51]. For more details about ligand interactions in the orthosteric binding site, please see [36,[51][52][53]. Ligand interactions with residues located in LB2 seem to be restricted to agonists and high-affinity antagonists [36,52,53].…”
Section: Orthosteric Binding Sitementioning
confidence: 99%
“…For more details about ligand interactions in the orthosteric binding site, please see [36,[51][52][53]. Ligand interactions with residues located in LB2 seem to be restricted to agonists and high-affinity antagonists [36,52,53]. Interactions with residues in both LB1 and LB2 are likely to be a requirement for activation, and cause the agonists to become buried within the closed receptor conformation (Figure 3).…”
Section: Orthosteric Binding Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Since the PROPKA software is slightly sensitive to the ligand pocket geometry, the steps of hydrogen addition/withdrawal and energy minimization are carried out until no difference is observed in the protonation results. 26 …”
Section: Methodsmentioning
confidence: 99%